FLUID FILTRATION TO MULTI-BORE HORIZONTAL WELLS IN A DEFORMABLE POROUS MEDIUM - Zhumagulov Bakytzhan,; Masanov Zhailau,; Azhikhanov Nurlan Tobahanovich,; Zhunissov Nurseit Muchidinovich,; Bekbolatov Alimzhan Berikbayevich, (Scientific Journal of Pedagogy and Economics, 2019)
The scientific work considers finite element modeling of fluid filtration in a deformable porous medium. A transversely isotropic medium has been taken as a deformable medium. Fluid filtration process to a horizontal well in the transversely isotropic medium has been analyzed. Numerical solution of the problem is carried out by high-performance finite element modeling